Home Health Care Logistics Management: Framework and Research Perspectives - Gutiérrez, E. Valentina; Gutiérrez, Valentina; Vidal, Carlos J. (International Journal of Industrial Engineering and Management, 2013)
Home Health Care (HHC) services are a growing sector in the medical service business. These services are based on a delivery network in which patients are hospitalized at their homes and health care providers must deliver coordinated medical care to patients. The fact that patients and medical staff’s homes are considered as a component of the delivery network creates a difference from typical health care organizations and generates a greater complexity on logistics decisions. In this paper we provide a reference framework for HHC logistics management in order to identify research perspectives in the field. With this framework we present a brief review of the current literature in models and methodologies used to support logistics decisions and identify research gaps. In particular, we emphasize the need to develop and implement more integrated methodologies to support decisions at tactical and strategic planning levels and to consider key features from real systems. Article history: Received (22 October 2012); Revised (21 December 2012); Accepted (15 March 2013)